The preventive effect of Nigella sativa seed on gastric ulcer induced by indomethacin in rat - Maryam Paseban; Saeed Niazmand; Mohammad Soukhtanloo; Naser Tayyebi Meybodi (Shahrekord University of Medical Sciences, 2020)
Introduction: Nonsteroidal anti-inflammatory drugs (NSAIDs) are considered as one of the most administrated groups of medications worldwide. Due to the role of NSAIDs in inducing gastric ulceration, their clinical applications are still challenging. Nigella sativa seed is widely used as an herbal medication against gastrointestinal complications. The present experiment was carried out to investigate the impact of N. sativa seed hydro-alcoholic extract on gastric ulcer induced by indomethacin (IND) and to evaluate its possible mechanisms in rat. Methods: This study was performed on 48 male Wistar rats. Acute gastric ulceration was induced by IND (35 mg/kg). N. sativa seed extract (100, 200, 400 mg/kg) and ranitidine (50 mg/kg) were administered orally for five days before the induction ulcer. Ulcer index, gastric acid secretion, gastric mucus content, glutathione (GSH), malondialdehyde (MDA), total hexose, gastric juice protein content were determined on the fifth day. Results: The ulcer index in all groups of N. sativa seed was significantly lower than that of the IND group. N sativa seed considerably decreased MDA and protein content, but increased total thiol, total hexose, and mucus content compared to the IND group. N. sativa seed did not affect gastric acid secretion. Conclusion: These findings were indicative of the gastroprotective effect of N. sativa seed against the IND-induced ulcer, suggesting that it can mainly be exerted through the anti-oxidant activity of the extract as well as its role in stimulating gastric mucus secretion and increasing total hexose in the gastric mucosa.